Effects of the Farmland-to-Forest/Grassland Conversion Program on the Soil Bacterial Community in the Loess Hilly Region - Chen, Meng-Li; Zeng, Quan-Chao; Huang, Yi-Mei; Ni, Yin-Xia (Huanjing kexue, 2018)
This study investigated the effects of the program aimed at converting farmland into forest or grassland on the soil bacterial diversity in the Loess Hilly region. Corn land was selected as the experimental control, and land and land were selected as the experimental lands. Soil from three different land use types were selected as subjects. The soil bacterial communities were analyzed using a high throughput sequencing technique (MiSeq). The sequence region was 16S rRNA V3-V4 variable region. The diversity, community composition, and relative abundances of the soil bacterial groups were analyzed, in order to explore the effects of soil physical and chemical properties on the bacterial community structure. The results showed that the structure and diversity of the microbial communities differed under the different land use types. At the phylum level, the dominant phyla were Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, Gemmatimonadetes, and Firmicutes. At the class level, -Proteobacteria, Actinob